The Principle of Beneficence of Doctor-Patient Communication Regarding the Implementation of the Hospital Code of Ethics in Health Services - Purwati, Ani; Ruslita, Gita (Journal of Law, Politic and Humanities, 2025)
The principle of beneficence as the main ethical basis in medical practice plays an important role in building communication between doctors and patients according to the hospital code of ethics. This article carefully analyzes how beneficence plays a role as an ethical obligation as well as a legal norm in the provision of health services. Based on normative legal analysis and a cross-disciplinary approach, the discussion shows the obligation of doctors to prioritize patient welfare, not only through clinical actions, but also through honest, empathetic communication, and based on informed consent. In the Indonesian context, which is characterized by social and cultural diversity and changes in digital health services, the implementation of beneficence must be able to overcome structural and ethical challenges. This study also describes how hospital-oriented ethical governance, such as the Hospital Ethics and Law Committee, can implement the principle of beneficence to avoid malpractice and strengthen public trust in health institutions. The latest empirical data and international policy frameworks such as the Universal Declaration of Bioethics and Human Rights from UNESCO, this article suggests a model of ethical communication as an important element of justice in health services. Finally, beneficence must be institutionalized not only as a personal contribution, but also as a systematic standard that ensures fair, empowering, and rights-based patient care.